Using model-based systems engineering for the electronic logging device regulation - Adeboyejo, Adedapo David, author; Daily, Jeremy, advisor; Herber, Daniel, committee member; Johns, Brian, committee member (Colorado State University. Libraries, 2026)
This thesis demonstrates the utility of model-based systems engineering (MBSE) and model-based structured requirements (MBSR) for evaluating and improving the Electronic Logging Device (ELD) regulation governing hours-of-service (HOS) tracking for commercial motor vehicle drivers, as codified in Title 49 of the Code of Federal Regulations (CFR) Chapter III Part 395 [1]. This study demonstrates the use of MBSE to develop a representative system architecture model of the existing ELD system in the Systems Modeling Language (SysML v1.7) and the application of MBSR to model and evaluate regulatory requirements. The approach is tested by mapping specific regulatory sections of the CFR to corresponding model elements and comparing the presence of structured pattern elements in existing CFR requirements and FMCSA guidance documents. The results affirm that MBSR provides an iterative approach to evaluating the clarity of the ELD regulation, particularly when integrated into a model understanding. This systematic approach enhances the baseline understanding of the current system while preparing for adaptations to improve future ELD systems, with an emphasis on security and fraud reduction, issues that compromise highway safety.
Zip file contains 3 MDZIP and 1 BAK files.
Keywords: electronic logging device; model-based structured requirements; systems engineering; Federal Motor Carrier Safety Administration; Code of Federal Regulations; model-based systems engineering